ZnO thin films prepared on titanium substrate by PLD technique at different substrate temperatures. (7th May 2014) - Zeng, Yong; Zhao, Yan; Jiang, Yijian
<x xml:space="preserve">Abstract</x> ZnO thin films were grown by pulsed laser deposition on titanium substrates at different substrate temperatures ranging from 300 to 700 °C. X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), photoluminescence, and Raman spectroscopy are employed to investigate the change of properties. XRD, XPS, and Raman data showed that the films consisted of TiO2 at high substrate temperature, which will deteriorate the crystallization quality of ZnO films. The optimum temperature for the growth of ZnO films on the Ti substrate is about 500 °C in this paper. The ZnO films grown on titanium substrate can be used in direct current, microwave, and medical applications. Copyright © 2014 John Wiley & Sons, Ltd.